Binding Effect of Cassava Starches on the Compression and Mechanical Properties of Ibuprofen Tablets - Judith Chitedze, Maurice Monjerezi, JD Kalenga Saka, Jan Steenkamp (Journal of Applied Pharmaceutical Science)
Starch is the most common binder in tablet formulations and important sources include cassava tubers. Using cassava starches extracted from three different cultivars (Mbundumali, Mulola and Sauti), the effect of native cassava starches as binders on the compression and mechanical properties of ibuprofen tablets was studied. The starches were used as binders for 400 mg ibuprofen tablets produced by wet granulation at the various concentrations (2-8 %w/w) and compressed at different punch settings (23-27). The formed tablets were evaluated for hardness, friability and disintegration. Cassava starches, derived from the three cultivars can be used as binders in uncoated ibuprofen tablets under the following operating conditions: punch setting of 24 and binder concentration of 2% w/w. Under such conditions, less friable tablets were produced and reduced amounts of materials were used. Mulola starch is the most appropriate binder for ibuprofen tablets while Sauti starch could be useful when fast disintegration is more essential and a requirement.
Keywords: compression, tableting, excipients, mucilage, cassava starch, ibuprofen.